Sistema de seguridad de equipos de laboratorío - Domínguez Espinoza, Juan (2009)
The main objective of this project is to develop a security system for laboratory equipment. This consists on the design of a system which allows users to monitor the equipment continuously, as well as, the implementation and testing of a small scale prototype designed to emulate the behavior of the system. The security system uses a wireless identification module named RFID (Radio Frequency Identification) which allows the identification from some distance of an electronic tag that periodically emits a radiofrequency signal to the RFID reader module. In addition to RFID technology an Ethernet communication module is used. This will send data collected by the RFID sensor to a desktop computer. That uses LabVIEW as virtual instrumentation software. Communication between the RFID sensor and the Ethernet communication module is possible through the implementation of a chip that contains the Ethernet’s libraries and it connects through SPI with a microcontroller 18F4520 optimizing the functioning of the security system and ensuring proper processing of the data.